Perancangan Sistem Informasi Arsip Perencanaan (SIAP) Berbasis Web di Biro Perencanaan Kementerian Perhubungan - Farhan Aditya; Sandfreni Sandfreni (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
The SIAP Application is an innovation developed as a solution to support the archiving business process in the Planning Bureau. Currently, most employees still use computers and a web-based cloud system developed by Pusdatin using the PHP programming language as a storage medium for files that are no longer actively used and are categorized as dynamic archives. However, the cloud system does not have a well-structured archive management system, which often causes difficulties when employees need to retrieve archived files. As a result, employees must search for files manually by checking archived documents one by one in the cloud. This process is time-consuming and may lead to problems such as difficulties in finding files and the risk of data loss. Based on these conditions, the SIAP Application was developed to improve the effectiveness and efficiency of archive management in the Planning Bureau.The SIAP Application has an advantage in the archiving process, where employees can easily search for archives using the letter number or subject that has been entered into the system. The system will automatically display the required archive, making the retrieval process faster, more accurate, and more organized compared to the previous cloud system.The development of the SIAP Application uses PHP and HTML as the programming languages, with Bootstrap and Tailwind CSS as the user interface frameworks, and MySQL as the database. The system development method used is the Waterfall model, problem analysis is carried out using the PIECES method, and system testing is conducted through black-box testing and the System Usability Scale (SUS) to measure system usability.